The application of geomatics in the teaching of geography in tenth grade - Espín-Curbelo, Jennifer (2025)
This research addresses the relevance of the transformation of the Cuban education system, within the framework of the Third Improvement of the National Education System, with a focus on the incorporation of Geomatics into tenth-grade geography teaching. The objective was to propose activities that enhance the application of Geomatics to improve spatial learning and contribute to sustainable development. The sample consisted of 24 students from the "Osvaldo Herrera" Pre-University in Santa Clara, Cuba, selected for presenting difficulties in spatial interpretation. Methods such as document review, classroom observation, and interviews were employed, applying methodological triangulation to ensure validity. The results show that the students showed interest and basic knowledge, although with deficiencies in cartographic skills and teamwork. The designed activities fostered cognitive development, motivation, and spatial analysis skills, contributing to meaningful learning and strengthening civic values. The discussion highlights that geomatics facilitates the management of geospatial data, promotes environmental awareness, and fosters essential skills for territorial management. It is concluded that integrating geospatial technologies into geographic education is vital for training future professionals who are aware and competent, contributing to contemporary social and environmental challenges.